1986
DOI: 10.1007/bf01869723
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium transport in medullary thick ascending limb of rabbit kidney: Involvement of the Na+, K+, Cl−-cotransporter

Abstract: In order to investigate the question whether ammonium reabsorption in the thick ascending limb of Henle's loop (TALH) proceeds via the Na+,K+,Cl(-)-cotransporter, plasma membrane vesicles were prepared from TALH cells isolated from rabbit kidney outer medulla and the effect of NH+4 on their transport properties was investigated. It was found that, in the presence of a 78-mmol/liter NaCl gradient, 5 mmol/liter NH+4 inhibited bumetanide-sensitive rubidium flux by 86%; a similar decrease was observed for 5 mmol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 13 publications
4
86
0
Order By: Relevance
“…1 and 2). Taken together with the fact that NH' has been shown to share the Na'-K+-2Cl-cotransporter in several cell types (14)(15)(16), including salivary glands, these results provide strong evidence that this enhancement of pHi recovery is due to increased NH14 entry into the acinar cytoplasm via the cotransporter, and thus indicate that isoproterenol treatment results in an upregulation of cotransporter activity.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…1 and 2). Taken together with the fact that NH' has been shown to share the Na'-K+-2Cl-cotransporter in several cell types (14)(15)(16), including salivary glands, these results provide strong evidence that this enhancement of pHi recovery is due to increased NH14 entry into the acinar cytoplasm via the cotransporter, and thus indicate that isoproterenol treatment results in an upregulation of cotransporter activity.…”
Section: Resultsmentioning
confidence: 60%
“…In order to do so, we employed a novel method for monitoring cotransporter activity. Briefly stated, we have taken advantage of the fact that NH' can substitute for K+ on the cotransporter (14)(15)(16). This made it possible for us to follow cotransporter activity via the changes in intracellular pH associated with cotransporter-mediated dissipation of NH' gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of ammonium by the medullary thick ascending limb occurs predominantly by secondary active transport, mediated by sub- Fig. 1 stitution of NHZ for K+ on the apical membrane Na'-K+-2 CVcotransport system (1,(40)(41)(42). The previous observation that vasopressin stimulates apical Na'-K+-2 Cl-uptake in mouse and rat medullary thick ascending limbs (6,21,30) suggested that NH' uptake via the cotransporter also might be accelerated.…”
Section: Resultsmentioning
confidence: 97%
“…Due to a similar hydrated radius, NH 4 + is known to substitute for K + in the NKCC and the NKA in a variety of different tissues (Kinne et al, 1986;Kurtz and Balaban, 1986;Towle and Holleland, 1987;Wall et al, 1995). NKA has been implicated in the basolateral uptake of ammonia in the collecting duct of the mammalian kidney (Kurtz and Balaban, 1986;Wall and Koger, 1994) and similarly, basolateral gill Na + /NH 4 + exchange via NKA has been suggested from studies on the toadfish (Claiborne et al, 1982;Mallery, 1983).…”
Section: Nkamentioning
confidence: 96%